Dead space and weaning from invasive mechanical ventilation in high-altitude residents - Viruez-Soto, José Antonio (2020)
Objective: To determine the predictive value of the dead space calculation through the dead space/tidal volume fraction at weaning from invasive mechanical ventilation in critically ill patients at high altitude. Materials and methods: An epidemiological, observational, analytical and prospective study carried out in the Adult Intensive Care Unit of the Hospital del Norte in the city of El Alto, Bolivia (4,090 m a.s.l.; barometric pressure: 453 mm Hg) from November 01, 2016 to March 31, 2017. High-altitude residents under invasive mechanical ventilation were studied. The inclusion criteria were: a) Altitude residents hospitalized in the Invasive Mechanical Ventilation Therapy Intensive Care Unit. b) Patients with evidence of resolution of the cause that prompted their connection to the invasive mechanical ventilator. c) Patients with positive weaning criteria and rates. d) Positive spontaneous respiration test. The study variables were the dead space through the Vd/Vt fraction and its relationship with the success or failure of the weaning process from mechanical ventilation. The Vd/Vt fraction was calculated in the study patients and then weaning from invasive mechanical ventilation was performed. Patients were divided into two groups according to the need for reintubation and reconnection to themechanical ventilator within 72 hours. Results: Twenty-one (21) patients were included: 7 (33 %) women and 14 men (67 %). The mean age was 41 years with a standard deviation of 22.38 years. Eighteen (18) patients (86 %) succeeded and 3 (14 %) failed in the weaning process from invasive mechanical ventilation. The Vd/Vt values in the success and failure groups were 0.43 and 0.53 (p < 0.011109), respectively, with a sensitivity of 0.61 and specificity of 1; a positive predictive value of 1 and a negative predictive value of 0.3. Conclusions: The calculation of the dead space through the measurement of the dead space/tidal volume fraction predicts the success of weaning of critically ill patients under invasive mechanical ventilation at high altitude.